A Journey through Manufacturing and Supply Chain Strategy Research A Tribute to Professor Gianluca Spina - Bartezzaghi, Emilio; Cagliano, Raffaella; Caniato, Federico; Ronchi, Stefano; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The book is a 'Liber Amicorum' for the late Gianluca Spina, Professor at Politecnico di Milano, Italy, who was well-known and respected in the European Operations Management research community. It consists of reprints of 7 of his most important cited and representative papers, spanning his research career from the early 90s and presenting his research trajectory. Each paper has original comments by one or two relevant international scholars in the field, who were also his close friends. These offer a critical discussion of the papers' content, as well as a discussion of their contribution to the academic debate since publication.
"The Impact of the Just-in-Time Approach on Production System Performance: A Survey of Italian Industry" by CiprianoForza and Roberto Filippini -- "Strategically flexible production: the multi-focused manufacturing paradigm" by Chris Voss -- "Advanced Manufacturing Technologies and Strategically Flexible Production" by Harry Boer -- "A model of codesign relationships: definitions and contingencies" by Alberto De Toni and Guido Nassimbeni -- "E-business strategy: how companies are shaping their manufacturing and supply chain through the Internet" by Matteo Kalchschmidt and AnnVereecke -- "Logistics and supply chain management in luxury fashion retail: empirical investigation of Italian firms" by Andrea Vinelli, amelaDanese and Pietro Romano -- "Past, present and future trends of purchasing and supply management: An extensive literature review" by Finn Wynstra and Michael Essig.
Keywords: Industrial Management; Production management; Operations research; Management science; Manufactures; Industrial Management; Operations Management; Operations Research, Management Science; Machines, Tools, Processes